Chestnut and acorn starch properties affected by isolation methods - Correia, Paula Reis; Beirão-da-Costa, Maria Luísa (Starch - Stärke, 2010)
Starches from chestnut (Castanea sativa Mill.) and acorns (Quercus suber Lam. and Q. rotundifolia Lam.) were isolated from dried fruits using four different methods. These involved a physicochemical and/or an enzymatic treatment followed by centrifugation and sieving: (i) low shear at alkaline pH – LSA, (ii) high shear in water – HSW, (iii) enzymatic treatment at low shear – LSE, (iv) LSA and using successively three sieves – LSA3S. Raw yield, purity, colour parameters, morphology, protein, fat, ash, reducing sugars and amylose contents, damaged starch content and viscoamylographic proﬁles were studied in isolated starches, presenting different properties through different methods. In general, chestnut starch seems to be poorly resistant to extraction methodologies as shown by the damaged starch content and viscoamylographic properties encountered during this study. Moreover, acorn starches exhibited cross-linked amylographic patterns. For all the tested raw materials, the LSA3S isolation method always higher yield and purity of starches. Gelatinization temperature and peak consistency were also higher than those shown by starches produced by the other methods, a less damaged structure was also evident. In conclusion, it seems that this method is the most suitable to produce starch for food ingredient usage.
Keywords: acorn; chestnut; morphology; physicochemical properties; starch isolation methods